2015
DOI: 10.1111/hel.12200
|View full text |Cite
|
Sign up to set email alerts
|

Helicobacter pylori Eradication in Patients with Immune Thrombocytopenic Purpura: A Review and the Role of Biogeography

Abstract: Idiopathic thrombocytopenic purpura (ITP) is typically a diagnosis of exclusion, assigned by clinicians after ruling out other identifiable etiologies. Since a report by Gasbarrini et al. in 1998, an accumulating body of evidence has proposed a pathophysiological link between ITP and chronic Helicobacter pylori (H. pylori) infection. Clinical reports have described a spontaneous resolution of ITP symptoms in about 50% of chronic ITP patients following empirical treatment of H. pylori infection, but response ap… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
54
0
6

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 64 publications
(61 citation statements)
references
References 137 publications
1
54
0
6
Order By: Relevance
“…In most cases, the association has not been shown to be causal, and common conditions will inevitably coexist in some patients. There are modest data linking H. pylori to immune thrombocytopenic purpura, and eradication therapy is often tried, with variable results 35 …”
Section: Prevalence Of Helicobacter Pylori Infection In Australia Andmentioning
confidence: 99%
“…In most cases, the association has not been shown to be causal, and common conditions will inevitably coexist in some patients. There are modest data linking H. pylori to immune thrombocytopenic purpura, and eradication therapy is often tried, with variable results 35 …”
Section: Prevalence Of Helicobacter Pylori Infection In Australia Andmentioning
confidence: 99%
“…5 Because H. pylori , the human gastric pathogen, has been linked to thrombocytopenia in select patients, the monkey was treated with a H. pylori eradication antibiotic therapy consisting of clarithromycin 15 mg/kg PO BID and amoxicillin 20 mg/kg PO BID for 10 days, and omeprazole 0.6 mg/kg PO SID for 21 days. 6 Antibiotic treatment for the H. suis infection did not resolve the coagulopathy and the episodes of petechiae +/− ecchymoses recurred. Although there was negative silver staining on gastric tissue collected during necropsy, 16S rRNA revealed that this antibiotic treatment did not completely eradicate the Helicobacter infection.…”
Section: Case Presentationmentioning
confidence: 96%
“…While a definitive mechanism by which H. pylori may induce thrombocytopenia remains elusive, proposed pathways include molecular mimicry of CagA by host auto antibodies against platelet surface glycoproteins, as well as alterations in the phagocytic activity of monocytes (Frydman et al, 2015).…”
Section: Iggmentioning
confidence: 99%